DAMPAK PEMUTIHAN PAJAK, DIGITALISASI, SOSIALISASI, DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN MEMBAYAR PAJAK KENDARAAN BERMOTOR (PKB) BANYUMAS, JAWA TENGAH - Firdaus, Abidah Fajar; Mustafa, Rasyid Mei (Business, Accounting and Management Journal, 2023)
This research was conducted to determine the impact of implementing Banyumas Government policies in increasing compliance with paying motor vehicle taxes after the COVID-19 pandemic. The policies influencing compliance will be analyzed further by achieving targets previously set as a benchmark for policy success. Policies deemed successful will be continued for the next period. The research concluded that (1) Tax bleaching has an effect on increasing compliance with paying motor vehicle tax, (2) Tax digitalization has no effect on compliance with paying motor vehicle tax, (3) Tax socialization has an effect on increasing compliance with paying motor vehicle tax, (4) Awareness Taxpayers do not influence compliance with paying motor vehicle taxes. The government's policy to increase motor vehicle tax revenue can be continued with tax bleaching programs and tax socialization with social media, which have proven to be quite effective in increasing motor vehicle tax revenue and compliance in Banyumas, Jawa Tengah.